Extending the Low Frequency Limit of Tightly Coupled Dipole Arrays for Ultra-Wide Bandwidth With Ultra-Thin Profile - Rajbala Solanki; Peng Khiang Tan; Theng Huat Gan (IEEE Access)
This paper proposes a flexible PCB based design for an ultra-wideband tightly coupled dipole array (TCDA) with an ultra-thin profile. The design approach involves increasing the capacitance between the dipole and the coupling patch, which compensates for ground inductance and effectively lowers the low frequency, thereby enhancing the bandwidth. The proposed configuration integrates a TCDA on an ultra-thin flexible PCB, a resistive frequency selective surface (FSS), and a balun (i.e. BALanced to UNbalanced feed transformation) constructed using a tapered microstrip line (MSL). By incorporating the FSS layer, ground reflection effects are effectively mitigated, leading to improved bandwidth. Additionally, the use of an ultra-thin flexible PCB (explored for the first time in TCDAs, to the best of our knowledge) allows the TCDA to extend its low frequency limit, further contributing to bandwidth enhancement. However, utilizing an ultra-thin flexible PCB poses fabrication challenges, such as maintaining uniform separation from the ground plane and difficulties with soldering etc. Numerical simulations indicate that the TCDA array achieves a bandwidth of approximately 24:1. The overall profile of the array is approximately $λ _{L}$ /25, (where $λ _{L}$ is the wavelength at the lowest frequency of operation) and it has an average radiation efficiency of 66%. To verify the accuracy of the simulation results, an $8.5× 8.5$ array prototype is fabricated and measurements are performed. The measured results closely align with the simulated outcomes.